2004
DOI: 10.1071/rd04088
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and imaging to assess oocyte and preimplantation embryo health

Abstract: Two major criteria are currently used in human assisted reproductive technologies (ART) to evaluate oocyte and preimplantation embryo health: (1) rate of preimplantation embryonic development; and (2) overall morphology. A major gene that regulates the rate of preimplantation development is the preimplantation embryo development (Ped) gene, discovered in our laboratory. In mice, presence of the Ped gene product, Qa-2 protein, results in a fast rate of preimplantation embryonic development, compared with a slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…In previous studies, HLA-G has been found colocalized in lipid rafts in JEG-3 cells (32). To facilitate focus on the cell membrane of the embryo and locate any HLA-G that may be present in low copy number, we double surface stained some embryos with cholera toxin B conjugated with Alexa Fluor-488 and MEM-G/9-PhyE.…”
Section: Spfi To Investigate the Spatial Distribution Of Hla-g In Prementioning
confidence: 99%
“…In previous studies, HLA-G has been found colocalized in lipid rafts in JEG-3 cells (32). To facilitate focus on the cell membrane of the embryo and locate any HLA-G that may be present in low copy number, we double surface stained some embryos with cholera toxin B conjugated with Alexa Fluor-488 and MEM-G/9-PhyE.…”
Section: Spfi To Investigate the Spatial Distribution Of Hla-g In Prementioning
confidence: 99%
“…Qa-2 has structural and immunological characteristics similar to those of HLA-G. Reportedly, Qa-2 can increase the rate of development of early embryos and assist in their survival (23), as well as protect tumor cells from NK cell-and lymphokine-activated killer cell-mediated cytolysis (24). However, the relationship of Qa-2 expression with immunosuppressive agents and graft rejection remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Last, several research groups have focused on building new tools for image rendering and analysis for biological data mining. Although this is a vast area of research, I have included references for a small sampling of papers and reviews to provide examples of ongoing research (Lansford et al, 2001;AlKofahi et al, 2002AlKofahi et al, , 2003Jacobs et al, 2003;Megason and Fraser, 2003;Herskovits et al, 2004;Huang and Murphy, 2004;Warner et al, 2004;Ledesma-Carbayo et al, 2005;Liebling et al, 2005;Lin et al, 2005;Peng et al, 2005;Suhling et al, 2005;Toga, 2005;Tyszka et al, 2005a;Forouhar et al, 2006;Luders et al, 2006).…”
Section: Tools For Image Analysismentioning
confidence: 99%